Postnatal Acute Famine and Risk of Overweight: The Dutch Hungerwinter Study - Annet F. M. van Abeelen; Sjoerd G. Elias; Tessa J. Roseboom; Patrick M. M. Bossuyt; Yvonne T. van der Schouw; Diederick E. Grobbee; Cuno S. P. M. Uiterwaal (Hindawi Limited, 2012)
Objective. To examine the association between undernutrition during postnatal periods of development and the risk of overweight in adulthood. Methods. We studied 8,091 women from Prospect-EPIC, exposed to the Dutch famine at ages between 0 and 21 years, recruited at ages between 49 and 70 years. We used linear and logistic regression models to explore the effect of famine on BMI, waist circumference, and the risk of overweight. Results. Overall, postnatal famine exposure was associated with increased BMI and waist circumference in a dose-dependent manner (𝑃fortrend<0.01). Furthermore, risk of overweight was increased following famine exposure (𝑃fortrend=0.01), with those severely exposed at ages 0-9 years having 25% (95% CI 1.05 to 1.50) higher risk compared to unexposed women. Conclusions. This study is the first to directly show a positive association between short and transient undernutrition during postnatal development and BMI, waist circumference, and overweight in adulthood.